Distribution of species from the genus Panorpa (Mecoptera, Panorpidae) in European Russia except the Caucasus - Dvořák, Libor; Ruchin, Alexander B.; Egorov, Leonid V.; Aleksanov, Victor V.; Alekseev, Sergey K.; Shulaev, Nikolai V.; Zakharova, Elena Yu (Nature Conservation Research: Заповедная наука, 2023)
The study of the insect distribution in geographical areas is relevant since it is important in terms of understanding the global trend of biodiversity decline. The paper presents the results of a study on the distribution of six species of Panorpidae (Mecoptera), carried out in 2008, 2009, 2011, 2015, 2017–2020. One part of data was collected by the authors. Other material was provided by colleagues from 11 regions in Russia. In European Russia, six species of Panorpa are reliably known, namely Panorpa alpina, P. cognata, P. communis, P. germanica, P. hybrida, and P. vulgaris. The most common and frequently encountered species are P. communis (in 21 regions), P. hybrida (in 12 regions), P. vulgaris (in 11 regions), and P. cognata (in 11 regions). It is assumed that all studied species can be found in other regions of European Russia as a result of further investigations. Among the studied species, P. alpina and P. germanica are the rarest species, recorded from two and one regions, respectively. Panorpa vulgaris was found for the first time in Russia.